A Decision-Support Model for Football Squad Optimization: Integrating AHP-WASPAS and Binary Programming - Gultom, Parapat; Ezra, Posman; Marpaung, Jonathan Liviera; Weber, Gerhard Wilhelm; Sentosa, Ilham (Journal of Research in Mathematics Trends and Technology, 2025)
Team composition in professional football remains a critical challenge due to subjective biases and the complexity of player performance metrics. This study proposes a multi-criteria decision-making (MCDM) approach to optimize the starting lineup of PSIS Semarang. The Analytical Hierarchy Process (AHP) was used to determine the importance of positional attributes, followed by the Weighted Aggregated Sum Product Assessment (WASPAS) to evaluate individual player preferences. A binary integer programming model was developed to construct the optimal eleven-player formation. The proposed formation was validated through simulation in Football Manager 2023. Results showed that a 4-3-3 formation consistently outperformed alternatives, leading to first-place rankings and a President’s Cup win in simulation trials. This integrated decision-support model demonstrates effectiveness in enhancing team selection strategies in professional football.